2019
DOI: 10.5194/acp-2019-155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertical distribution of atmospheric particulate matters within urban boundary layer in southern China: size-segregated chemical composition and secondary formation through cloud processing and heterogeneous reactions

Abstract: Abstract. Great progress has been made recently in the understanding of the sources and formation mechanisms of atmospheric aerosols at the ground level. However, vertical profiles and sources of size-resolved particulate matter within the urban boundary layer are still lacking. In this study, vertical distribution characteristics of size-segregated particles were investigated at three observation platforms (ground, 118 m and 488 m) on the 610-meter-high Canton Tower in Guangzhou, China. Size-segregated aeroso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Printer-friendly version Discussion paper crometeorological measurements (including an important vertical wind speed) were not undertaken making it impossible to derive fluxes (refer to papers by (Valiulis, Ceburnis et al 2002, Ceburnis, O'Dowd et al 2008).…”
Section: Interactive Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Printer-friendly version Discussion paper crometeorological measurements (including an important vertical wind speed) were not undertaken making it impossible to derive fluxes (refer to papers by (Valiulis, Ceburnis et al 2002, Ceburnis, O'Dowd et al 2008).…”
Section: Interactive Commentmentioning
confidence: 99%
“…(Ovadnevaite, Manders et al 2014, Cravigan, Ristovski et al 2015 Line 19. One of the earliest papers published by (Valiulis, Ceburnis et al 2002) which also estimated emissions from the observed gradients.…”
Section: Minor Commentsmentioning
confidence: 99%